World, Symbol, Gaze - Zhuang Qi (Art and Society, 2024)
As it is written in the Bhagavad Gita: 1 The mind wanders, It’s restless at any moment, It needs to be controlled, Accept self-discipline. The three texts in this portfolio follow a critical, reflexive, and self-constraining first- person perspective. They are, in order: the “World” text, the “Symbol” text, and the “Gaze” text, with the “World” text as the starting point. The “World” text specifically analyzes Khyentse Norbu’s narrative film, Travellers and Magicians, and points out the Māyā characteristics of film. The “Symbol” text reflects on the distance between human and the God by combining semiotics and personal experience of devoting self to Buddhism with a research method that is mutually referenced with the Perennial philosophy. Finally, inspired by the first two texts, the “Gaze” text is a summative and complementary text. It takes Benjamin’s research as a starting point to reflect on the ritual value of contemporary spiritual films. These three texts point to each other and suggest a research style and methodology that is closely linked to personal experience, religion, and art.